The effects of a multi-lingual approach: an exploratory study with Year 9 - Sheppard, S (2021)
In the context of an increasingly multilingual and diverse society, there has been a move within European language education and research to adopt a more multilingual and holistic approach to modern languages, where languages are not taught in isolation, but where students are encouraged to compare and contrast their languages and make use of their ‘whole language repertoire’ from both school and home. Much of the work on this so far has either been theoretical, or projects in quite different contexts to the UK secondary MFL classroom, with a lack of evaluation of the effects of such projects on attitudes towards learning languages and students’ knowledge about language and ability to see connections between languages. My project therefore developed a multilingual approach for a UK context, that would work within the everyday MFL classroom. The activity of translation was chosen as the most appropriate way to get students to compare multiple languages. My school has already adopted this kind of approach for Year 7, so I wanted to see if something could be developed for Year 9, who are in many ways at a pivotal point in their language-learning career, as they go on to select which language(s) they will study for GCSE. With this in mind, the project aimed to see if adopting a multilingual approach in translation would have a positive impact on student attitudes and motivation, as well as their cross-linguistic awareness (XLA) and language-learning skills. The results from the quantitative data revealed that although the project did not have a measurable impact on students’ XLA or their already positive attitudes towards MFL, it did appear to have an impact on their ability to spot patterns in a new language. Results from the qualitative interview and observation data also showed the beginnings of an impact on students’ XLA, and the project will be subsequently expanded across the whole of Years 8 and 9 to further explore the potential impacts of this multilingual approach.